Pemberian Adok/Gelaran: Akulturasi Budaya Islam pada Tradisi Suku Komering Sumatera Selatan - Indah Ratu Sehati; Hudaidah Hudaidah (PT Inovasi Penelitian Terpadu, 2025)
The purpose of this study was to determine the Komering Tribe community in South Sumatra in giving adok or title as a form of Islamic cultural acculturation. The honorary title system known as the adok tradition is attached to a person's social identity based on descent, status, and role in the traditional community. After that, Islamic teachings entered the structure and symbols of this tradition, creating a blend of values ​​between Islamic teachings and local customs. This study uses ethnographic methodology and a qualitative approach with in-depth interviews, participatory observation, and documentation research in the South OKU area. The results of the study indicate that the acculturation of Islamic culture is seen in the embedding of titles containing Arabic elements, the use of Islamic prayers in customary processes, and changes in values ​​that emphasize morality and honor based on Islamic teachings. The tradition of giving adok is a way to maintain local cultural identity and harmonize customs and religion in the Komering community.